Transformation of the learning environment for children with special needs - Verónica Margarita Trillo Espinoza; Milyausha Shaimardanova; Irina Shakhmalova; Evgeniya Garina (Institute of Advanced Engineering and Science, 2023)
This study is devoted to the consideration of the issue related to the adaptation and adoption of such children in the Russian Federation. The study is based on the questionnaire method. It was attended by 120 parents of children with special needs. The results showed that the majority of respondents are familiar with inclusive education, its principles and goals; 59% of respondents believe that the psychological environment in their school is not good enough for the adaptation of children with special needs. According to 64% of parents, there are also problems with the infrastructure of schools. The minority of parents face the rejection of special needs children by teachers, but the majority face the rejection by their peers. In general, despite all problems and challenges, parents positively assess the idea of their special needs child learning and attending the same classroom side by side with healthy children. According to them, this has a positive effect on the intellectual and mental development of the child. To improve the process, the parents of such children were offered the following recommendations: constant research on the issue, cooperation with other parents of special needs children, attention to children and cooperation with specialists (psychologists and defectologists).